2013
DOI: 10.1007/s13197-013-1196-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and antioxidant enzymes status of rats fed on n-3 PUFA rich Garden cress (Lepidium Sativum L) seed oil and its blended oils

Abstract: Garden cress (Lepidium sativum L) seed oil (GCO) is a rich source of α-linolenic acid (ALA, 33.6 %) and the oil has a fairly balanced SFA, MUFA and PUFA ratio. In this study we have investigated the effect of GCO and its blends with n-6 PUFA rich edible vegetable oils sunflower oil (SFO), rice bran oil (RBO) and sesame oil (SESO) on antioxidant status of oils and antioxidative enzymes in Wistar rats. Physical blending of GCO with n-6 PUFA rich vegetable oils (SFO, RBO and SESO) increased content of natural ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Our data showed that administration of 400mg/kg EEGS along with HFD for six weeks evoked antioxidant activity, and this was indicated by the upregulation of hepatic SOD, CAT activity and GSH concentration along with a significant decrease in MDA and nitric oxide content. These findings are consistent with those reported previously by others (Umesha and Naidu, 2015;Questi et al, 2016;Al-Sheddi et al, 2016). Added to this, phenolic compounds and flavonoids possess hydroxyl groups that contribute to their antioxidant potential (Bendary et al, 2013;Panche et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data showed that administration of 400mg/kg EEGS along with HFD for six weeks evoked antioxidant activity, and this was indicated by the upregulation of hepatic SOD, CAT activity and GSH concentration along with a significant decrease in MDA and nitric oxide content. These findings are consistent with those reported previously by others (Umesha and Naidu, 2015;Questi et al, 2016;Al-Sheddi et al, 2016). Added to this, phenolic compounds and flavonoids possess hydroxyl groups that contribute to their antioxidant potential (Bendary et al, 2013;Panche et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…possesses antioxidant, hypoglycemic, hepatoprotective, cardioprotective, antidiarrheal, and anticancer activity (Al-Sheddi et al, 2016;Raish et al, 2016;Ullah et al, 2019). Feeding GC seed oil supplementation for 60 days than natural oil in rats, Umesha and Naidu (2015) reported higher levels of hepatic tocopherols, catalase, and glutathione peroxidase activity. Following oral supplementation of 20%GC methanol seed extract (w/v) for 28 days in streptozotocin-induced diabetic rats, Qusti et al (2016) observed an increased renal and pancreatic activity of SOD, CAT, GSH, and a decreased MDA contents.…”
mentioning
confidence: 99%
“…Alqahtani et al [3] stated that L. sativum seed oil showed a high potentiality of reducing lymphocyte reproduction and the production of inflammatory mediators. Umesha and Naidu [30] demonstrated that feeding of rats with garden cress seed fixed oil, and garden cress seed fixed oil blended with other oils significantly increased it's antioxidant enzymes. Garden cress seed fixed oil contains a high amount of cis-10-heptadecenoic acid, which is reported as an anticancer [28].…”
Section: Introductionmentioning
confidence: 99%
“…Since natural antioxidants have an inherent safety advantage, there is increasing interest concerning the use of natural antioxidants to replace synthetic antioxidants. These antioxidants can be separated from many natural products such as herbs [ 5 , 6 ], vegetables [ 7 ], and fruits [ 8 ]. Mushrooms are also potential sources of antioxidants [ 9 11 ], and there is an increasing focus of therapeutic evidence for medicinal mushrooms in their use as anticancer [ 12 15 ] and antiviral [ 16 , 17 ] agents.…”
Section: Introductionmentioning
confidence: 99%